2001
DOI: 10.1021/np000441w
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins Isolated from Angelica gigas Inhibit Acetylcholinesterase:  Structure−Activity Relationships

Abstract: Acetylcholinesterase (AChE) inhibitory activity-guided fractionation of Angelica gigas led to isolation and identification of a new coumarin, peucedanone (12), and isolation of 11 known coumarins. Among them, decursinol (1) represented the highest inhibitory activity toward AChE in vitro. The correlation of the inhibitory activities of the coumarins toward AChE with their chemical structures was studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(141 citation statements)
references
References 20 publications
8
130
0
3
Order By: Relevance
“…12) Likewise, Kang et al found that coumarin derivatives (for example methoxsalen, isoimperatorin, and decursinol) from Angelica gigas inhibited AchE activity as well. 13) As far as we know, the present study is the first in vivo trial to study the relationship between methoxsalen and its ability to ameliorate memory impairment by modulating AchE activity.…”
Section: Discussionmentioning
confidence: 88%
“…12) Likewise, Kang et al found that coumarin derivatives (for example methoxsalen, isoimperatorin, and decursinol) from Angelica gigas inhibited AchE activity as well. 13) As far as we know, the present study is the first in vivo trial to study the relationship between methoxsalen and its ability to ameliorate memory impairment by modulating AchE activity.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, several coumarin derivatives, including decursins, decursinol, decursinol angelate, nodakenin, nodakenetin, and umbelliferone, were isolated from Angelica gigas [7,19,24]. Additional pharmacological effects of these derivatives include anti-tumor activities [2,17,22], antiplatelet aggregation [25], Helicobacter pylori-suppression [3], neuroprotection [20], and memory enhancement [21,43].…”
mentioning
confidence: 99%
“…The effects of skin moisturizing are easily detectable by water content through animal skin or human pilot study 18,19) . 36) . Rehmanniae Radix contained Catalpol, Verbascose and Mannitol, and Catalpol was reported as having an anti-oxidation effect 37) .…”
Section: Groupsmentioning
confidence: 99%